Catalytic Conversion of Furan to Hydrocarbons using HZSM‐5: Coking Behavior and Kinetic Modeling including Coke Deposition. Issue 1 (12th July 2016) - Shao, Shanshan; Zhang, Huiyan; Xiao, Rui; Shen, Dekui
Abstract: Coke deposition is the biggest barrier that hinders the hydrocarbon yields during the catalytic pyrolysis of biomass. The proposed pathway studied here yields benzofuran as a primary product, all the olefins and aromatic hydrocarbons as secondary products, and polycyclic aromatic hydrocarbons as tertiary products. The product selectivity only changed with catalytic temperature and coke deposition, whereas no effect was observed if the weight hourly space velocity and partial pressure were varied. The curve of conversion versus coke content in the catalytic conversion of furan follows an exponential trend [i.e., Φ =exp(‐ αC )] which indicates that the catalytic conversion of furan exhibits fast deactivation. A kinetic model considering coke deposition has been built based on the above reaction pathway to correlate the product distribution with the coke content, and the final correlation coefficients (>0.96) indicate good agreement. Abstract : Coke deposition matters : A catalytic fast pyrolysis pathway is proposed with benzofuran as a primary product, all olefins and aromatic hydrocarbons as secondary products, and polycyclic aromatic hydrocarbons as a tertiary product. The product selectivity changes with temperature and coke deposition, whereas no effect is observed if the weight hourly space velocity and partial pressure are varied. A kinetic model considering coke deposition is built to correlate the product distribution with coke content.